Synthesis and photophysical properties of fullerene-phthalocyanine- porphyrin triads and pentads - Enes, Roger F.; Cid, Juan-Jose; Hausmann, Anita; Trukhina, Olga; Gouloumis, Andreas; Vazquez, Purificacion; Cavaleiro, Jose A. S.; Tome, Augusto C.; Guldi, Dirk Michael; Torres, Tomas (Chemistry - A European Journal, 2012)
The synthesis and photophysical properties of several fullerene- phthalocyanine-porphyrin triads (1-3) and pentads (4-6) are described. The three photoactive moieties were covalently connected in an one-step synthesis through 1,3-dipolar cycloaddition to C of the corresponding azomethine ylides generated in situ by condensation reaction of a substituted N-porphyrinylmethylglycine derivative and an appropriated formyl phthalocyanine or a diformyl phthalocyanine derivative, respectively. ZnP-C -ZnPc (3), (ZnP) -ZnPc-(C ) (6), and (H P) -ZnPc-(C ) (5) give rise upon excitation of their ZnP or H P components to a sequence of energy and charge-transfer reactions with, however, fundamentally different outcomes. With (ZnP) -ZnPc-(C ) (6) the major pathway is an highly exothermic charge transfer to afford (ZnP)(ZnP )-ZnPc- (C )(C ). The lower singlet excited state energy of H P (i.e., ca. 0.2 eV) and likewise its more anodic oxidation (i.e., ca. 0.2 V) renders the direct charge transfer in (H P) -ZnPc-(C ) (5) not competitive. Instead, a transduction of singlet excited state energy prevails to form the ZnPc singlet excited state. This triggers then an intramolecular charge transfer reaction to form exclusively (H P) -ZnPc -(C )(C ). A similar sequence is found for ZnP-C -ZnPc (3). Copyright © 2012 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.